Brain theory : biological basis and computational principles - Aertsen, Ad. (Adrianus), 1948-; Braitenberg, Valentino; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1996)
The present collection of papers focuses on the subject of vision. The papers bring together new insights and facts from various branches of experimental and theoretical neuroscience. The experimental facts presented in the volume stem from disparate fields, such as neuroanatomy, electrophysiology, optical imaging and psychophysics. The theoretical models in part are unsophisticated, yet still inspiring, while others skilfully apply advanced mathematical reasoning to results of experimental measurements. The book is the fifth in a series of volumes intending to define a theory of the brain by bringing together formal reasoning and experimental facts. The reader is thus being introduced to a new kind of brain science, where facts and theory are beginning to blend together.
Includes bibliographical references.
Print version record.
Elsevier
Keywords: Visual cortex; Visual perception; MEDICAL -- Neuroscience; PSYCHOLOGY -- Neuropsychology; Visual cortex; Visual perception; Visual Cortex; Visual Perception -- physiology; Humans -- Brain -- Physiology; Electronic books